Significance of silica analysis in groundwater studies of domestic shallow wells in parts of Jeli district, Kelantan, Malaysia - Mohammad Muqtada Ali Khan; Fatin Wahida Fadzil; Hafzan Eva Mansor; Dony Adriansyah Nazaruddin; Zameer Ahmad Shah (Springer International Publishing, 2016)
The present study was carried out to investigate the nature and behaviour of silica in shallow groundwater in parts of Jeli district, Malaysia to assess the groundwater and surface-water interaction, to determine the depths, residence duration of groundwater and to evaluate groundwater contamination by correlating silica with hydrochemistry and the temperatures at which groundwater has acquired present silica concentrations. The most important factors controlling Silica concentration in the groundwater is the rock type with which water comes in contact and most importantly the duration of interaction. In the present study, silica concentrations analysed in 7 samples exhibit an average value of 14 mg/l. Such silica concentrations clearly indicate the minimal impact of anthropogenic activities and small residence time of groundwater in terms of rock-water interaction. Prolonged rock-water interaction would have resulted in acquisition of high silica concentrations as the area is mostly covered by igneous rocks. Such low silica values (7 to 21mg/l) also point to the influent nature of the rivers in the area where surface water has caused the smoothening of silica concentrations in groundwater. By employing silica geo-thermometry, the maximum temperature estimated is about 33°C which under normal geothermal conditions would corresponds to a depth of 0.20 km (200 meter) by considering an average heat flow of 30 °C/km. Such shallow depths (below 0.20 km) of groundwater circulation are pretty reasonable for such deficient silica concentrations.